In pursuit of these theories Authoritarianism, relative deprivation, and intergroup contact. [article]. - Pettigrew, Thomas F.
Throughout my career, I have pursued three theories related to intergroup prejudice-each with a different mentor. Each theory and its supporting research help us to understand prejudice and ways to ameliorate the problem. This autobiographical review article summarizes some of the advances in these three areas during the past six decades. For authoritarianism, the article advocates removing political content from its measurement, linking it with threat and dismissive-avoidant attachment, and studying how authoritarians avoid intergroup contact. Increased work on relative deprivation made possible an extensive meta-analysis that shows the theory, when appropriately measured, has far broader effects than previously thought. Increased research attention to intergroup contact similarly made possible a meta-analysis that established the pervasive effectiveness of intergroup contact to reduce prejudice under a wide range of conditions. The article closes by demonstrating how the three theories related to each other and contribute to our understanding of prejudice and its reduction. - (from the authors)
Keywords: Prejudice; Authoritarianism; Relative deprivation; Intergroup contact; Gordon Allport; Samuel Stouffer